2014
DOI: 10.1007/s00203-014-1059-y
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and bioprospecting of culturable actinomycetes from marine sediment of the Yellow Sea, China

Abstract: Marine actinomycetes are a potential source of a wide variety of bioactive natural products. In this work, seven pretreatments, three selective isolation media, and five artificial seawater concentrations were used to isolate actinomycetes from the sediments collected from Yellow Sea, China. Statistical analysis showed that only the isolation medium strongly affected the total and bioactive numbers of actinomycete isolates. A total of 613 actinobacterial strains were isolated and screened for antimicrobial act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…Most of the 17 abundant OTUs had less than 97% identity with their closest isolates, hinting that these abundant species in the marine sediment might be uncultured (Table 2 ). A total of 613 Actinobacteria stains had been isolated from the same marine sediment and 105 16S rRNA sequences had been released in previous study (Xiong et al, 2015 ). However, among all the 105 16S rRNA sequences, only three16S rRNA sequences (The Genbank accession numbers are JQ924069 , JQ924085 , and JQ924089 , 100% identity of these 3 sequences) showed more than 95% identities with one OTU (containing 2 reads, and they showed 99.1 and 100% identities with these 3 sequences, respectively) identified in this study, suggesting that Actinobacteria bacteria identified by culture independent method were different from previously identified culturable Actinobacrteria in the same sample.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the 17 abundant OTUs had less than 97% identity with their closest isolates, hinting that these abundant species in the marine sediment might be uncultured (Table 2 ). A total of 613 Actinobacteria stains had been isolated from the same marine sediment and 105 16S rRNA sequences had been released in previous study (Xiong et al, 2015 ). However, among all the 105 16S rRNA sequences, only three16S rRNA sequences (The Genbank accession numbers are JQ924069 , JQ924085 , and JQ924089 , 100% identity of these 3 sequences) showed more than 95% identities with one OTU (containing 2 reads, and they showed 99.1 and 100% identities with these 3 sequences, respectively) identified in this study, suggesting that Actinobacteria bacteria identified by culture independent method were different from previously identified culturable Actinobacrteria in the same sample.…”
Section: Resultsmentioning
confidence: 99%
“…The marine sediment samples were collected at the depth of 50–100 m in the summer of 2010 from several adjacent sites of undisturbed environment in the Yellow Sea sediment close to Rizhao, Shangdong province, China (Xiong et al, 2015 ). They were stored in sterilized plastic bags after being taken from the deep sea and transported to the laboratory at 4°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the Streptomyces species further explored produced three diketopiperazine dimers, including the new dimer isonaseseazine B 107, a stereoisomer of naseseazine B. 83,84 A modied diketopiperazine 108 with antimalarial properties was isolated from a Streptomyces sp. isolate from the Florida Keys as part of the outcome of screening a large collection of microorganisms for antiproliferative and antiplasmodial properties.…”
Section: Introductionmentioning
confidence: 99%
“…ROVs with their visual inspection capabilities and the precise manipulators enable targeted sampling to investigate specific features such as microbial communities along an anthropogenic disturbance gradient (Nguyen et al, 2017), meio-and macrofaunal organism diversity along temperature gradients at a hydrothermal vent (Sarrazin et al, 2015), and geochemical, microbial, meio-and macrofaunal sampling of specific habitats on an unexplored lobe of the Congo deepsea fan (Rabouille et al, 2017). Deep oceanic sediments, hydrothermal vents, and cold-seeps are host to high levels of microbial diversity that are sources of unique biocatalysts able to withstand high pressure and variable temperatures (Duncan et al, 2015;Jensen et al, 2005;Xiong et al, 2015). Microbial communities present grow in extreme cold (psychrophilic), heat (thermophilic) (Urbieta et al, 2015), pressure (barophilic), salt (halophilic) (Yin et al, 2015) or acidic (acidophilic) conditions.…”
Section: Q9 How Can We Develop Emerging Industries In the Deep Sea?mentioning
confidence: 99%